2005
DOI: 10.1016/j.ejcts.2005.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic surgery for hydrothorax in peritoneal dialysis patients — check-air-leakage method

Abstract: Hydrothorax developing from pleuroperitoneal communication as a complication of peritoneal dialysis was first described in 1967 [Edward SR, Unger AM. Acute hydrothorax-a new complication of peritoneal dialysis. JAMA 1967; 199:853-5. ]. The incidence of hydrothorax is approximately 1.6-2% of continuous ambulatory peritoneal dialysis (CAPD) patients. The key to successful therapy is obliteration of the transdiaphragmatic route of dialysate leakage with video-assisted thoracoscopic surgery (VATS). The method in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
(5 reference statements)
0
7
0
1
Order By: Relevance
“…Thus, we used the following three methods to detect them: (1) carefully checking the leakage of the CAPD solution; (2) checking the leakage of the dye-added CAPD solution; (3) using a technique called the check-air-leakage method. 3 In our case, the former two methods successfully detected the lesion. Yen et al reported that the sensitivity of the check-airleakage method is high, 3 but we were unable to detect the lesion using that method.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, we used the following three methods to detect them: (1) carefully checking the leakage of the CAPD solution; (2) checking the leakage of the dye-added CAPD solution; (3) using a technique called the check-air-leakage method. 3 In our case, the former two methods successfully detected the lesion. Yen et al reported that the sensitivity of the check-airleakage method is high, 3 but we were unable to detect the lesion using that method.…”
Section: Discussionmentioning
confidence: 59%
“…3312; Fax +81-11-613-7318 e-mail: makohashi1001@hotmail.co.jp used a technique called the check-air-leakage method. 3 We found no air leakage on the diaphragm with this method, not even from the two points that were already determined to be pleuroperitoneal communications.…”
Section: Casementioning
confidence: 92%
“…The third method is to identify the communication by fi lling the thoracic cavity with sterile water and monitoring air bubbles entering from the abdomen into the thoracic cavity. 8 Although this method is simple to perform, exact localization of the air bubbles entering the thorax may be quite diffi cult. Nonetheless, this third method can be a useful alternative if the fi rst two methods are not able to determine the location of the communication.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of video-assisted thoracoscopic surgery for PPC in CAPD patients have been published. 2,[5][6][7][8] However, few single-institutional reports discuss the details of surgery for PPC in CAPD patients including intraoperative findings, postoperative course, and outcomes. We experienced four surgical cases of PPC in CAPD patients since 2008, and our aim was to retrospectively analyze their clinical features as well as their intraoperative findings, postoperative course, and outcomes.…”
Section: Introductionmentioning
confidence: 99%